2005
DOI: 10.1103/physrevb.71.014502
|View full text |Cite
|
Sign up to set email alerts
|

Magnetothermopower and magnetoresistivity ofRuSr2Gd1xLaxCu

Abstract: We report measurements of magnetothermopower and magnetoresistivity as a function of temperature on RuSr 2 Gd 1-x La x Cu 2 O 8 (x = 0, 0.1). The normal-state thermopower shows a dramatic decrease after applying a magnetic field of 5 T, whereas the resistivity shows only a small change after applying the same field. Our results suggest that RuO 2 layers are conducting and the magnetic field induced decrease of the overall thermopower is caused by the decrease of partial thermopower associated with the spin ent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 28 publications
(4 reference statements)
1
40
0
Order By: Relevance
“…Due to the hole-mediated effective exchange interaction between Mn spins, the anisotropy fields in GaMnAs result from the coupling of several valence bands by the spin-orbit interaction and depend on the transient hole distribution and coherences between different bands [16]. In the static case, recent experimental [17] and theoretical [18] investigations have shown that increasing the hole density significantly reduces the cubic anisotropy (K c ) along the [100] direction, while enhancing the uniaxial anisotropy (K u ) along [1][2][3][4][5][6][7][8][9][10]. One therefore expects that the photoexcited hole population turns on an effective magnetic field pulse (∆B c ) along the [1][2][3][4][5][6][7][8][9][10] direction [ Fig.…”
mentioning
confidence: 99%
“…Due to the hole-mediated effective exchange interaction between Mn spins, the anisotropy fields in GaMnAs result from the coupling of several valence bands by the spin-orbit interaction and depend on the transient hole distribution and coherences between different bands [16]. In the static case, recent experimental [17] and theoretical [18] investigations have shown that increasing the hole density significantly reduces the cubic anisotropy (K c ) along the [100] direction, while enhancing the uniaxial anisotropy (K u ) along [1][2][3][4][5][6][7][8][9][10]. One therefore expects that the photoexcited hole population turns on an effective magnetic field pulse (∆B c ) along the [1][2][3][4][5][6][7][8][9][10] direction [ Fig.…”
mentioning
confidence: 99%
“…Equation (9) shows that this is the case for high dielectric constant, small spin stiffness, strong dependence of T c on carrier concentration, and rapid onset of magnetization below T c . For Ga; MnAs, we estimate T by comparing experiments [7,9] to mean-field theory for homogeneous magnetization [14] and to spin-wave theory [18]. We find T c ÿ T of the order of 10 K. The properties of Ga; MnAs vary strongly with Mn concentration and growth procedures.…”
Section: Prl 96 117201 (2006) P H Y S I C a L R E V I E W L E T T E mentioning
confidence: 99%
“…In Ref. [9], 5:4 10 5 K A 3 , which was used for the above estimate, whereas in Ref. [7], 1:5 10 5 K A 3 , which would increase T c ÿ T .…”
Section: Prl 96 117201 (2006) P H Y S I C a L R E V I E W L E T T E mentioning
confidence: 99%
See 1 more Smart Citation
“…When treating correlations in the realistic (III,Mn)V system, the numerical solution of the above closed system of equations of motion is complicated by the coupling of many momenta and bands and by unsettled issues regarding the role on the dynamical and magnetic anisotropy properties of impurity bands, strain, localized states, and sp-d hybridization [1,20,21,22,23]. In the simpler RPA case, which neglects inelastic effects, a sixband effective mass approximation [16] revealed an order of magnitude enhancement of D. The single-band RPA model [15] also predicts maximum D at very small hole concentrations, while in the six-band model D increases and then saturates with hole doping.…”
mentioning
confidence: 99%